Magic as a tool to build rapport with new environment: Herr Röslein trilogy by Silke Lambeck - Yuliya V. Krasovickaya (RUDN Journal of Studies in Literature and Journalism)
Investigates how a literary character adapts to a new context in the debut trilogy of the German writer Silke Lambeck ( Herr Röslein , 2007; Herr Röslein kommt zurück , 2008; Wo bleibt Herr Röslein? 2010). The aim is to look into the ways the child-character establishes rapport with the new environment backed by a wizard and his magical power and to define the distinctive features of the wizard and his young pupil. The analysis acknowledges that magic plays a crucial role in resolving conflicts and helps characters navigate and adapt to new foreign spaces and societies. Real life in the novels is not displaced by a fantasy world; the magician character just empowers others to become more confident in their own strength. A special focus is made on the process of Mr. Leopold Rosette’s magic powers transformation. In the third book the wizard’s responsibility to settle conflicts is passed on the child character Moritz. This makes magical powers modification: from now on magic is found in kind and courageous acts of the rescuer or wise decisions of the psychologyst. Magic itself as seen by the child appears as an amazing and at the same time frightening thing. Yet, magic does not serve as the main reference point in the surrounding world but rather performs a supporting function.